Functionalization of activated carbons by HNO3 treatment: Influence of phosphorus surface groups. - Ternero-Hidalgo, Juan José; Rosas-Martínez, Juana María; Palomo-Jiménez, José; Valero-Romero, María José; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás (Elsevier, 2016)
Influence of phosphorus on functionalization of activated carbons with nitric acid has been reviewed in this study. Results indicate that during treatment with nitric acid, phosphorus-containing carbons seem to graft more surface nitrogen, particularly as nitro groups, than those without phosphorus, where the nitrogen is found in lower oxidation state. A reaction pathway has been proposed to clarify the oxidation/nitration mechanism of phosphorus-containing carbons. The model consists of three independent mechanisms occurring simultaneously, with each one involving different phosphorus species present in the activated carbons.
https://openpolicyfinder.jisc.ac.uk/id/publication/16741
Keywords: Catalizadores; Carbón activado; Ácido nítrico; Functionalization; Nitric acid; Phosphorus; Activated carbon